Work Discipline, Organizational Culture Moderation, and Public Service Performance in The Pagelaran Community - Rachmat Rachmat; Neli Yuliawati (PT. Alahyan Publisher Sukabumi, 2026)
This study aims to analyze the effect of civil servants’ work discipline on public service performance, with organizational culture as a moderating variable, in the Pagelaran region. Public services in this area currently face challenges such as slow service processes and inconsistent implementation of Standard Operating Procedures (SOPs). The method used is an explanatory quantitative approach employing Structural Equation Modeling (SEM-PLS) analysis. The research sample consists of 125 respondents service users selected through purposive sampling. The results indicate that work discipline has a dominant, positive, and significant effect on public service performance. Organizational culture also has a direct positive influence on performance, although its contribution is not as substantial as that of work discipline. A key finding in this study reveals that organizational culture is unable to moderate or strengthen the relationship between work discipline and public service performance. This indicates the need for organizational culture transformation to better align with the values of work discipline in order to achieve responsive, transparent, and accountable service.